The effectiveness of a group counseling program to deal with cultural identity crisis among a sample of female adolescents in the Sultanate of Oman - AL- Hatmi, Sumiah Rashid Humaid (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to build a group counseling program and investigate its effectiveness to deal with the cultural identity crisis among a sample of adolescents in Dahira Province in the Sultanate of Oman. The researcher applied a scale of the cultural identity crisis designed to suit the purpose of selected sample of the study. This scale was applied on the applicants who participated in the counseling program. They were 60 female adolescents from Fatima bint Qais School for Basic Education, particularly from Post Education classes ( 11th and 12th ). The sample was divided randomly into two groups: the experimental group which consisted of 30 adolescents who received a counseling program which was designed to achieve the objectives of the study. The second group is the control group which equally consisted of 30 adolescents who didn't receive any treatment.The study used the group counseling program based on The Logo Therapy of Frankel (1967). This program consisted of 14 counselingsessions implemented during seven weeks with a maximum of two counseling sessions per week and for about 80 minutes for each session.Arithmetic means and standard deviations for all members of experimental and control group were computed for the cultural identity crisis scale and its five dimensions on the pre, post and follow- up measurements. A T- test analysis was used to examine the statistical significance of the differences in degrees of the cultural identity crisis between members of the experimental and control groups.The results of the study showed significant differences at (0.05≥α) in degrees of crisis between experimental and control groups members in both post and follow- up measurement in favor of the experimental group. This confirms the effectiveness of the group counseling program in reducing significantly the cultural identity crisis within members of experimental group.The results also showed significant differences at (0.05≥α) between members of experimental group in both pre and post measurements in favor of the post measurement.In addition, the result showed no significant differences in the degree of the cultural identity crisis among control group members by using both post and follow- up measurements. This demonstrates clearly the effectiveness of the group counseling program in dealing with the cultural identity crisis with adolescents in Oman.Moreover, the result showed significant differences at (0.05≥α) between the degrees the cultural identity crisis of the experimental group members due to their educational level in favor of the 12th grade.
Keywords: Group Counseling Program; Treatment; Cultural Identity Crisis; Adolescents